Targeting macrophages in atherosclerosis using nanocarriers loaded with liver X receptor agonists: A narrow review - Yang, Tong-Mei; Miao, Miao; Yu, Wen-Qian; Wang, Xue; Xia, Fang-Jie; Li, Yan-Jie; Guo, Shou-Dong (Frontiers in Molecular Biosciences, 2023)
Macrophages are involved in the whole process of atherosclerosis, which is characterized by accumulation of lipid and inflammation. Presently, clinically used lipid-lowering drugs cannot completely retard the progress of atherosclerosis. Liver X receptor (LXR) plays a key role in regulation of lipid metabolism and inflammation. Accumulating evidence have demonstrated that synthetic LXR agonists can significantly retard the development of atherosclerosis. However, these agonists induce sever hypertriglyceridemia and liver steatosis. These side effects have greatly limited their potential application for therapy of atherosclerosis. The rapid development of drug delivery system makes it possible to delivery interested drugs to special organs or cells using nanocarriers. Macrophages express various receptors which can recognize and ingest specially modified nanocarriers loaded with LXR agonists. In the past decades, a great progress has been made in this field. These macrophage-targeted nanocarriers loaded with LXR agonists are found to decrease atherosclerosis by reducing cholesterol accumulation and inflammatory reactions. Of important, these nanocarriers can alleviate side effects of LXR agonists. In this article, we briefly review the roles of macrophages in atherosclerosis, mechanisms of action of LXR agonists, and focus on the advances of macrophage-targeted nanocarriers loaded with LXR agonists. This work may promote the potential clinical application of these nanocarriers.